Child and parental physical activity: Is there an association with young children activity? - Voukia, Christina; Voutsina, Ismini; Venetsanou, Fotini; Kambas, Antonis (Central European journal of public health, 2018)
OBJECTIVES: The aim of the study is to examine the physical activity (PA) of young children and their parents on weekdays and at the weekend, as well as possible associations between them. METHODS: Fifty-eight children (29 boys), aged 5-8 years (mean age = 6.53 years) and the parent who spent more time with them (25 fathers, 33 mothers, mean age 40.67 years) wore Omron HJ-720IT pedometers for seven consecutive days. Two ANOVAs for repeated measures were applied to examine PA differences between genders and week phases (weekdays vs. weekend days) in children and parents. Moreover, one sample t-tests were used to compare participants' PA to the recommended PA, while linear regression analyses were utilized to examine whether parental PA in each week phase was associated with children's PA. RESULTS: Children accumulated more steps on weekdays than at the weekend (F1,56 = 18.58, p < 0.001, η2 = 0.27), while boys presented higher PA than girls (F1,56 = 12.42, p = 0.001, η2 = 0.20), and accomplished the recommended daily PA, in contrast to girls. Mothers and fathers presented similar PA (p = 0.67, η2 = 0.004), with more steps on weekdays than at the weekend (F1,56 = 9.22, p = 0.004, η2 = 0.16). However, their PA was significantly lower than the recommended. Finally, there were no statistically significant associations between parents' and boys' ambulatory activity either on weekdays (p = 0.938) or at the weekend (p = 0.095). On the contrary, parents' PA explained 47% of girls' PA on weekdays (R = 0.68, F1,28 = 22.81, p < 0.001) and 23% at the weekend (R = 0.48, F1,28 = 6.40, p = 0.02) Conclusions: Boys appear to be more physically active than girls in Greece, whereas mothers and fathers present similar ambulatory activity. Moreover, parents' PA is related to that of their daughters and not to that of their sons. Taking into account that both girls and parents did not meet PA recommendations, family-based interventions are needed for both children and parents benefit.
Keywords: Surveys and Questionnaires; Anthropometry; antropometrie; Humans; dítě; Child; steps; Female; health; dospělí; vztahy mezi rodiči a dětmi; lidé; family; ambulatory activity; průzkumy a dotazníky; pedometers; předškolní dítě; Adult; Řecko; ženské pohlaví; Greece; Male; Parent-Child Relations; Exercise; mužské pohlaví; cvičení; Child, Preschool